Soft mechanochemical synthesis and thermal stability of hydroxyapatites with different types of substitution - Natalya V. Eremina; Svetlana V. Makarova; Denis D. Isaev; Natalya V. Bulina (Chimica Techno Acta, 2022)
The feasibility of soft mechanochemical synthesis was studied here for hydroxyapatite with various types of substitution. It was shown that this method allows obtaining hydroxyapatites substituted with copper or iron cations and hydroxyapatites cosubstituted with zinc cations and silicate groups. Thermal stability of the synthesized samples was evaluated. It was found that to preserve phase homogeneity of the material, the temperature during the preparation of ceramic products and coatings should not exceed 600–800 °C. An exception is the hydroxyapatite where a hydroxyl group is expected to be replaced by a copper cation during the synthesis at a degree of substitution x = 0.5. For this sample, the temperature of the the heat treatment can be increased to 1100–1200 °C because copper cations return to the hydroxyapatite crystal lattice at these temperatures, and the material becomes single-phase.